Clonal haematopoiesis of indeterminate potential‐related mutations and outcome in dilated and ischaemic cardiomyopathy - Jasmine M.F. Wu; Tarek Bekfani; Anna Hinze; Julian Georg Westphal; Berit Steinacker; Max Zeller; Charlotte Hartmann; Sven Möbius‐Winkler; Andreas Hochhaus; P. Christian Schulze; Thomas Ernst (ESC Heart Failure, 2022)
Abstract Aims Clonal haematopoiesis of indeterminate potential (CHIP)‐associated mutation is a risk factor for the development of ischaemic cardiomyopathy (ICM), but its association with non‐ischaemic dilated cardiomyopathy (DCM) remains unclear. We aimed to determine the prevalence of CHIP in patients with DCM and define its risk for disease progression. Methods and results Next‐generation sequencing targeting 54 common CHIP‐associated genes was performed in 48 ICM and 52 DCM patients. The patients were monitored for a median of 3.1 years, and a COX proportional hazards model was used to examine the association between CHIP and adverse clinical outcome with regard to all‐cause death or all‐cause hospitalization. Overall, the prevalence of CHIP mutations was 19% and 13% in DCM and ICM, respectively. Seventeen per cent of ICM patients over 75 years were CHIP carriers. In DCM cohort, mutation event had already been observed in the patients who were under the age of 45 (13%). Among 54 genes analysed, DNMT3A had the highest mutation frequency, followed by TET2 and CUX1. Kaplan–Meier curve over a median of 3.1 year tracking period showed a trend towards poor clinical outcome in the DCM patients who carried DNMT3A or TET2 mutation; however, such association was not statistically significant. Conclusions The prevalence of CHIP is detected at a young age in DCM, and accumulation of mutational frequency in DCM patients is independent of age. However, a larger patient cohort is required to validate the association between CHIP and clinical progression in the DCM patients.